Intestinal obstruction complicated by large Morgagni hernia - B, Martín Arnau; R, Medrano Caviedes; S, Rofin Serra; F, Caballero Mestres; M, Trias Folch (Archives of Surgery and Clinical Research, 2017)
Morgagni hernia represents 2-4% of congenital diaphragmatic hernias. Only one-third of them are symptomatic, due to the hernia of abdominal viscera in the thoracic cavity, causing respiratory and digestive problems, some of them serious ones, such as intestinal obstruction. Acute presentation with incarceration of the contents is rare; there are only 7 cases described in the literature. We are presenting a case of diaphragmatic hernia that began with obstruction of the colon and secondary ischemia, requiring emergency surgery in two phases: first surgery to control the damage, with an open right hemicolectomy, and then later surgery to repair the hernia and perform bowel transit reconstruction, with proper postoperative evolution and no evidence of relapse. The treatment of Morgagni diaphragmatic hernia is surgical. Also in asymptomatic cases, due to the risk of incarceration, the most appropriate way to enter is abdominally, whether by way of laparotomy or laparoscopy, for the reduction of the contents of the hernia sac, the repair of the defect, as well as the performing of associated techniques on herniated viscera, as occurred in our case. A complicated congenital hernia is an infrequent pathology, and there is little experience in handling it. Acute presentation requires a combined treatment of the abdominal symptoms and repair of the hernia defect. The carrying over of surgical techniques for damage control into non-traumatic surgery in the face of serious hemodynamic instability is a widespread, accepted practice with the benefits of reducing mortality in critical patients and at times allowing the avoidance of ostomies.